EDUCATING SAVING EDUCATION FOR ELEMENTARY SCHOOL STUDENTS - Zulkarnain Lubis (Proceeding International Seminar of Islamic Studies, 2022)
Real Work Lecture is a form of community service activity by students with a cross-scientific and sectoral approach at a predetermined time and area. This report is a documentation of real work lectures for North Sumatra Muhammadiyah University students who were assigned to serve in Sidoharjo 1 Pasar Miring Village. This real work lecture activity is focused on educating saving in elementary schools which aims to provide an understanding of saving at an early age. This activity is located in Sidoharjo Village 1 consisting of rice fields, brick wards, rice barns and residential areas. The results of the research obtained that there are several efforts in educating saving on school students. First, by buying a savings or piggy bank for students. Second, by educating students to set aside or set aside pocket money given by their parents. Third, educate parents to provide or be a good role model for students at home.Keywords: Education , save and student